EFL Learners’ Perceptions on the Use of Flashcards in English Vocabulary Learning: A Lesson from Remote Schools - Nazira, Arni; Suciani, Pemy Ria; Dewi, Ni Luh Putu Meka; Wulandari, Ela (Journal of Language and Literature Studies, 2025)
Learning English vocabulary is quite challenging for students especially for young learners. Meanwhile it is essential for young learners in mastering English language. Because of that, the researcher gives one of the most effective media used in teaching vocabulary, that is flashcard media. This research specifically investigates how students perceive on the use of flashcards and what benefits it brings to the student’s vocabulary learning. In order to answer the research questions, this research employed a qualitative descriptive with case study type. In addition, the data were gained by both open-ended questionnaires that were shared to 20 students and phone interviewing 5 of them to gain insights into students’ experiences and attitudes towards media flashcards for learning vocabulary. The results showed that most of the students had good perceptions of the use of English Flashcard. They thought that English flashcard helped them to train their English vocabulary mastery. Using English flashcard, the students easier to memorize new words and enjoy in learning English vocabulary. Therefore, the students did not face any challenges in learning English vocabulary using flashcard. These findings imply that the use of flashcards in vocabulary learning can effectively improve young learners’ engagement, retention, and motivation. It means that, the students showed positive perceptions in learning English vocabulary using Flashcards. They also expect that the use of Flashcard can improve their ability in mastering English language.